2013 Humaine Association Conference on Affective Computing and Intelligent Interaction 2013
DOI: 10.1109/acii.2013.33
|View full text |Cite
|
Sign up to set email alerts
|

Automatically Recognizing Facial Indicators of Frustration: A Learning-centric Analysis

Abstract: Affective and cognitive processes form a rich substrate on which learning plays out. Affective states often influence progress on learning tasks, resulting in positive or negative cycles of affect that impact learning outcomes. Developing a detailed account of the occurrence and timing of cognitive-affective states during learning can inform the design of affective tutorial interventions. In order to advance understanding of learning-centered affect, this paper reports on a study to analyze a video corpus of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 25 publications
1
45
0
1
Order By: Relevance
“…However, failure to overcome obstacles in these situations can introduce a sense of mounting frustration in developers that can negatively impact learning outcomes [1] and influence retention in a field [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, failure to overcome obstacles in these situations can introduce a sense of mounting frustration in developers that can negatively impact learning outcomes [1] and influence retention in a field [2].…”
Section: Introductionmentioning
confidence: 99%
“…Open questions from the tutor (QO-TUTOR) with no student brow lowering (NoAU4) were positively predictive of engagement in the model with the combined bimodal feature set (Bimodal Union). Brow lowering has been previously associated with confusion, frustration, and mental effort [5,8,9,14]. Thus, this may highlight moments when the student was not perplexed by a tutor question.…”
Section: Engagementmentioning
confidence: 90%
“…CERT recognition is based on a support vector learning approach of frontal face images and includes pose correction. Grafsgaard et al [16] suggests that facial expression probabilities may vary significantly between individuals. In order to access this variation phenomenon we compared the machine facial expression analysis with the observer-and self-assessment.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…For the CERT assessment of emotion for computer-mediated tutorial dialogues Grafsgaard et al [16] reported the importance to perform a bias adjustment, due to inter-person variation. For this study we do not adjust this bias, since we intend to show the ability of our physical exergame to provoke emotions and show differences.…”
Section: Related Workmentioning
confidence: 99%